External Arguments and Dative Cliticization: Evidence of Selective Spell‐out of Functional Heads. (15th April 2016) - Kupula Roos, Mikko
Abstract: The paper discusses dative cliticization in Modern Greek in passives and unaccusatives. Based on crosslinguistic evidence, I show that dative cliticization is not implicated in movement operations that violate the Minimal Link Condition (MLC). Instead, the observed cliticization patterns exhaustively reduce to the effects of a generalized form of a Doubly Filled Comp Filter. In particular, I show applicative morphemes can be selectively overt also in Indo‐European languages like Greek and that the selective spell‐out of these morphemes positively correlates with the absence of external arguments (Spec, vP). The discussion posits an incremental spell‐out pattern for complex terminals and highlights the reality of head movement as a syntactic operation. The paper also revisits the claim that clitics constitute a heterogeneous class of items and that their morphosyntactic properties might depend on the transitivity/voice of the hosting predicate.